2002
DOI: 10.1677/joe.0.1720137
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of genistein on apoptosis induced by fluoride and pertussis toxin in human and rat pancreatic islets and RINm5F cells

Abstract: Clonal pancreatic -cell lines have been used widely for the study of the factors involved in the regulation of apoptosis but it has not been firmly established that the response of normal islets mirrors that found in transformed -cells. In the present work, the role of pertussis toxin (Ptx)-sensitive G-proteins in the control of -cell apoptosis was studied in isolated rat and human islets of Langerhans and compared with the clonal -cell line, RINm5F. Annexin-V and deoxycarboxyfluoroscein diacetate staining was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 35 publications
0
18
0
2
Order By: Relevance
“…We were unable to detect GADD45a at the protein level in uninduced INS-1 cells, although exposure of INS-1 cells to 5 mM NaF (which induces b-cell apoptosis (Elliott et al 2002)) resulted in the appearance of immunoreactive GADD45a. This suggests that, as in other cell types, GADD45a may play a role in regulating the apoptotic response of b-cells to certain stimuli.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…We were unable to detect GADD45a at the protein level in uninduced INS-1 cells, although exposure of INS-1 cells to 5 mM NaF (which induces b-cell apoptosis (Elliott et al 2002)) resulted in the appearance of immunoreactive GADD45a. This suggests that, as in other cell types, GADD45a may play a role in regulating the apoptotic response of b-cells to certain stimuli.…”
Section: Discussionmentioning
confidence: 57%
“…GADD45a protein was not detectable in control INS-1 cells, but its expression was clearly induced by NaF, a reagent that has previously been shown to cause apoptosis in islets and b-cell lines (Hollander et al 1999, Sheikh et al 2000, Elliott et al 2002, Hildesheim et al 2002. However, despite the evidence of increased GADD45a mRNA expression in response to WT HNF1b in microarray studies, no GADD45a protein was detectable after either 24 or 48 h of induction of the transcription factor (results not shown).…”
Section: Genes Involved In Hnf1b Induction Of Cell Deathmentioning
confidence: 95%
See 1 more Smart Citation
“…A positive role of tyrosine phosphorylation in the manifestations of toxic fluoride effects was established in A549 cells, where NaF-induced apoptosis was partially reduced by tyrosine kinase inhibitor genistein [26]. The proapoptotic effects of NaF in both RINm5F pancreatic cell line and human and rat pancreatic islet cells were also associated with the activation of genisteinsensitive tyrosine kinases [36,58]. In the fluoride-treated osteoblastic cells, pertussis toxin-insensitive G proteins were suggested to activate several cytoplasmic protein tyrosine kinases from Src family, Pyk2 (proline-rich tyrosine kinase 2) and Fak (focal adhesion kinase) [61,62], what modulates the adhesion properties of these cells and, consequently, differentiation, migration, and apoptosis.…”
Section: Tyrosine Phosphorylationmentioning
confidence: 98%
“…As early as in 1985, Blackmore et al [57] suggested that inhibition of some G protein (possibly Gα i ) by fluoroaluminate creates "some degree of regulatory chaos" in the rat hepatocytes. Lately, the role of Gα i protein in execution of toxic fluoride effects was demonstrated in the clonal RINm5F pancreatic β-cells and rat Langerhans islets, where apoptosis induced by 5 mM NaF was markedly enhanced by pretreatment with pertussis toxin (Ptx) modifying the α-subunit of Gα i/o family [35,36,58]. The rat proximal tubules also respond to fluoride through Gα i protein [59].…”
Section: G Protein-linked Signaling Pathwaysmentioning
confidence: 99%